Risk factors for uterine rupture in the UK. (7th June 2011) - Fitzpatrick, K E; Kurinczuk, J J; Alfirevic, Z; Spark, P; Brocklehurst, P; Knight, M
Abstract : Background: Recent reports of the risk of morbidity due to uterine rupture may have contributed to a decrease in the number of women attempting vaginal birth after caesarean section. The aims of this study were to estimate the incidence of true uterine rupture in the UK and describe the risk factors in women with prior caesarean delivery. Methods: A national population-based case-control study was undertaken using the UK Obstetric Surveillance System between April 2009 and April 2010. Results: 159 women with uterine rupture were identified; an estimated incidence of 1.9 per 10 000 maternities (95%CI 1.6 to 2.2). Among women with a previous caesarean delivery, the odds of uterine rupture were increased in women who had two or more previous caesarean deliveries (Adjusted OR (aOR) 2.59, 95%CI 1.01 to 6.63), less than 12 months between previous caesarean delivery and next pregnancy (aOR 3.13, 95%CI 1.65 to 5.94), placenta praevia (aOR 22.9, 95%CI 3.27 to 160.7) or planned to have a vaginal delivery (aOR 14.2, 95%CI 6.6 to 30.9). A higher risk of uterine rupture with labour induction and/or oxytocin use was apparent, with the highest odds in women who had both induction with prostaglandin and oxytocin used in labour (aOR 4.02, 95%CI 1.02 to 15.8) compared to women who laboured without prostaglandin or oxytocin. Conclusions: Uterine rupture, even among women with a previous caesarean delivery, is a rare occurrence. The risk increases with number of prior caesarean deliveries, a short previous caesarean-pregnancy interval and labour induction and/or augmentation and these factors should be considered when counselling women regarding mode of delivery in subsequent pregnancies.